Analisis Tingkat Pemahaman dan Kesadaran Mahasiswa terhadap Prinsip Kesetaraan Gender di Lingkungan Pendidikan Tinggi - M Rizky Ananda Hasibuan; Nurul Aini Harahap; Syarifah Khairatun Hisan (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
Examining how well college students grasp the concept of gender equality is the primary goal of this research. In order to achieve social justice and provide equal opportunity for all people, regardless of their gender, gender equality must be upheld. But there are still attitudes and actions that show gender disparity in the classroom. Students from different academic programs filled out questionnaires that were part of a descriptive quantitative research. The majority of pupils had a solid grasp of gender equality or its significance in the classroom, according to the data. Nevertheless, several respondents did not provide very detailed assessments of campus initiatives promoting gender equality.